Overstretching Expectations May Endanger the Success of the “Millennium Surgery” - Bender, Alwina; Damm, Philipp; Hommel, Hagen; Duda, Georg N. (Frontiers in Bioengineering and Biotechnology, 2022)
Total hip arthroplasty (THA) is an extremely successful treatment strategy. Patient expectations, however, have increased; if not properly guided by surgeons, at present, patients expect next to pain-free restoration of the joint and a fast return to work and sports. While the revision rates after THA also increased in younger patients, knowledge on musculoskeletal loads still remains sparse, and the current recommendations on postoperative rehabilitation are based on expert opinions only. The aim of this study was to unravel biomechanical contact conditions in “working age” (<60 years, 53.5 ± 3.0 years) and “retirement age” (>60 years, 67.7 ± 8.6 years) patients during activities recommended post-THA. We hypothesized that working age patients would show substantially increased hip contact loads compared to older patients. The in vivo joint contact force (Fres) and torsion torque (Mtors), reflecting the main contact load situation, experienced during activities of daily living and sports activities were measured in a unique group of 16 patients with instrumented THA. We summarized patient activities and sports recommendations after THA mentioned within the literature using PubMed (without claim of completeness). The measurements showed that younger working age patients experienced significant (p = 0.050) increased Mtors (21.52 ± 9.11 Nm) than older retirement age patients (13.99 ± 7.89 Nm) by walking. Bowling, as a recommended low-impact sport, was associated with Fres of up to 5436 N and Mtors of up to 108 Nm in the working age group, which were higher than the Fres (5276 N) and Mtors (71 Nm) during high-impact soccer. Based on our results, age was proven to be a discriminator in joint loading, with working age patients presenting with increased loads compared to retirement age patients, already during daily activities. The current patient recommendations have led to further increased joint loadings. If THA cannot be delayed in a patient, we propose counselling patients on a carefully considered return to sports, focusing on low-impact activities, as indicated hereby. The findings from this work illustrate the need to provide critical feedback to patient expectations when returning to work and sports activities. Patients returning to more intensive sports activities should be carefully monitored and advised to avoid as much overloading as possible.